Atypical deep somatic soft-tissue leiomyoma of extrathoracic chest wall: first case of the literature. Issue 1 (13th December 2018) - Batihan, Guntug; Usluer, Ozan; Kaya, Seyda Ors; Aydogdu, Zekiye
Abstract : Leiomyomas are benign soft-tissue tumours which take origin from the smooth muscles. Pleura and chest wall are uncommon location for such tumours. Here, we report a case of a 26-year-old female patient presented with 3 months history of chest pain. Chest X-ray and CT showed a calcified mass of 6×12 cm in size in the left lateral of the chest wall. After resection of the mass, pathological examination diagnosed it as atypical deep somatic soft-tissue leiomyoma of extrathoracic chest wall. No pathological finding was detected during follow-up.